POPULAR FEAST IN THE SOUTH OF MINAS GERAIS AND THE CULTURAL DIVERSITY OF THE SACRED IN THE MUNICIPALITIES OF MACHADO AND SILVIANÓPOLIS - Corrêa, Jhonatan Silva; Alves, Flamarion Dutra (Geosaberes; Vol 13 (2022), 2022)
This article seeks to show the diversity existing in the festivities linked to the sacred and the profane in the South of Minas Gerais. In the approach was foucused on existing cultural diversity in the municipalities of Machado and Silvianópolis, two importante festivities for the cultural scenario. Each city has its specificity in the region, where a more concentrated and external atitude of Machado contributed to cultural development invested in its suits and expanded its cultural influence for neighboring cities. Silvianópolis more descentralzed and importer, in the consolidation of its sacred spaces and symbolic intineraries groups a mixture of manifestations in its composition, not failing to contribute with other parties, but has as a specificity to import the suits from other municipalities. For the development of work, bibliographic research and fieldwork was essential with observations and aplications of semi-structured interviews with the aim of understanding this cultural diversity linked to the sacred space in the festivities in the municipalities studied and its importance and contribution to the cultural scenario.